1993
DOI: 10.1017/s0003356100006395
|View full text |Cite
|
Sign up to set email alerts
|

The bioavailability of magnesium from different types of calcined magnesites of Greek origin

Abstract: The objective of this work was to determine the apparent bioavailability of magnesium from four different types of calcined magnesites of Greek origin. These four types (A, B, C, D) were different in particle size fractions and production process. The solubility of the above four magnesium samples and their fractions were determined: (a) in the laboratory using ammonium nitrate solution after 24-h shaking and (b) in vivo using a nylon bag technique after 24-h incubation. Solubility was correlated with appare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…Solubility in molar ammonium nitrate of magnesites calcined at different temperatures tended to be better correlated with urinary magnesium output than with apparent availability. However, there were correlations between solubility and both availability and (more significantly) with urine output for particle size fractions, in agreement with Zervas & Papadopoulos (1993). Whilst Durrant & Draycott (1976) have reported that solubility in molar ammonium nitrate is of value in assessing magnesium availability in fertilizer-grade calcined magnesites for sugarbeet, this may be more suitable for much larger particle sizes and over the long growing period of the crop.…”
Section: Effects On Blood Magnesium Concentrations Of Lactating Ewes supporting
confidence: 68%
See 1 more Smart Citation
“…Solubility in molar ammonium nitrate of magnesites calcined at different temperatures tended to be better correlated with urinary magnesium output than with apparent availability. However, there were correlations between solubility and both availability and (more significantly) with urine output for particle size fractions, in agreement with Zervas & Papadopoulos (1993). Whilst Durrant & Draycott (1976) have reported that solubility in molar ammonium nitrate is of value in assessing magnesium availability in fertilizer-grade calcined magnesites for sugarbeet, this may be more suitable for much larger particle sizes and over the long growing period of the crop.…”
Section: Effects On Blood Magnesium Concentrations Of Lactating Ewes supporting
confidence: 68%
“…The extent of loss of materials calcined at different temperatures was well correlated with both urinary magnesium output and availability. Zervas & Papadopoulos (1993) did not establish such a relationship using four granular magnesites of mixed particle size (Greek origin) with fistulated sheep given hay and concentrates and using bags of 30-60 urn mesh. The potential value of a nylon bag method of appraisal will depend on the use of standardized conditions and recognition that different particle size fractions may have different rates of passage through the rumen.…”
Section: Effects On Blood Magnesium Concentrations Of Lactating Ewes mentioning
confidence: 97%
“…Such changes in polarity reduce the driving force for electropositively charged Mg ions to be taken up by rumen epithelial cells. In another study, 16 investigators used a wider range of particle sizes and determined that MgO was most soluble at a particle size < 500 µm, moderately soluble at 500 to 1,000 µm, and poorly soluble at > 1,000 µm. Because of the high amounts of potassium in many feedstuffs, especially forages, rations for lactating dairy cattle should contain high concentrations of Mg.…”
Section: Factors To Consider When Formulating a Dairy Ration To Meet mentioning
confidence: 99%